Irradiation crosslinking low-smoke halogen-free insulating material for automobile internal wire and preparation method thereof
By using the formula of irradiating, cross -linked low smoke and halogen -free insulating material in the internal wire insulation material of the car, the existing insulation materials have the lack of high and low -low flame retardant performance, and achieve better mechanical performance and comprehensive performance. Meet the high performance requirements of the internal wires of new energy vehicles.
Patent Information
- Application Number
- CN202411519666.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-24
AI Technical Summary
Existing automotive internal wire insulation materials such as PVC have halogen harmful substances, are easy to decompose, and have poor high and low temperature resistance. In addition, the radiation crosslinked halogen-free flame retardant polyolefin materials have a high proportion of flame retardant additives and poor processing performance during processing. It is difficult to meet the comprehensive requirements of the internal wires of the car.
A radiation cross-linked low-smoke halogen-free insulation material for automobile internal wires is used. The formula includes 15 to 55 parts of base resin, 1 to 10 parts of compatibilizer, 45 to 65 parts of flame retardant, 1 to 6 parts of filler, 0.5~1.35 parts Antioxidant, 2 to 5 parts of lubricant and 1 to 3 parts of cross-linking sensitizer. The filler is selected from at least one of organic montmorillonite and calcium carbonate silica masterbatch. By modifying organic montmorillonite Improve dispersion and optimize component ratio to improve high and low temperature resistance.
The insulation material has the characteristics of low smoke and halogen, good high temperature resistance, good flame retardant performance, and can improve the mechanical performance and comprehensive performance of insulating material on the basis of reducing the amount of flame retardant, and meet the needs of the internal wires of the car.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of insulating materials, and in particular to a radiation cross-linked low-smoke halogen-free insulating material for internal electric wires of automobiles and a preparation method thereof. Background Art
[0002] The current global automotive industry is developing rapidly, and new energy vehicles have gradually moved towards mass production from their rise in the past few years. In the field of new energy vehicles, my country's automotive industry is in a stage of rapid development, and the performance requirements for automotive internal wires are also gradually increasing. Automotive internal wires are used in high and low temperature and oily environments for a long time, so the insulation material of the outer layer of the wire needs to have comprehensive properties such as high and low temperature resistance, oil resistance and flame retardancy.
[0003] Most of the existing automotive internal wires use PVC (polyvinyl chloride) as insulation material, but PVC contains harmful substances such as halogens, and PVC is easy to decompose and has poor high and low temperature resistance. In addition, the EU's low-smoke and halogen-free replacement requirements for automotive internal wires have partially restricted the use of PVC insulation materials in automotive internal wires. Based on this, in recent years, the insulation material of automotive internal wires has begun to use radiation cross-linked halogen-free flame-retardant polyolefin materials, but in the processing of radiation cross-linked halogen-free flame-retardant polyolefin materials, there are problems such as high proportion of flame retardant addition and poor processing performance, which makes it difficult to meet the comprehensive requirements of automotive internal wires. Summary of the invention
[0004] In order to overcome the above disadvantages, the purpose of the present invention is to provide a radiation cross-linked low-smoke halogen-free insulating material for automotive internal wires and a preparation method thereof. The insulating material has the characteristics of low smoke and halogen-free, good high and low temperature resistance, and good flame retardant performance, and can meet the comprehensive requirements of automotive internal wires.
[0005] In order to achieve the above purpose, one of the technical solutions adopted by the present invention is: a radiation cross-linked low-smoke halogen-free insulating material for automotive internal wires, which comprises, by weight: 15 to 55 parts of base resin, 1 to 10 parts of compatibilizer, 45 to 65 parts of flame retardant, 1 to 6 parts of filler, 0.5 to 1.35 parts of antioxidant, 2 to 5 parts of lubricant and 1 to 3 parts of cross-linking sensitizer; wherein the filler is selected from at least one of organic montmorillonite and calcium carbonate silica gel masterbatch.
[0006] The beneficial effects of the radiation cross-linked low-smoke halogen-free insulating material for automobile internal wires of the present invention are: A filler is introduced into the formula of the insulating material, and the filler is selected from at least one of organic montmorillonite and calcium carbonate silica gel masterbatch to improve the carbonization of the insulating material, and can synergize with the flame retardant to enhance the flame retardant performance and high and low temperature resistance of the insulating material, thereby improving the mechanical properties of the insulating material on the basis of reducing the amount of flame retardant, thereby improving the comprehensive performance of the insulating material.
[0007] Specifically, the insulating material includes, by weight, 25-45 parts of base resin, 1-8 parts of compatibilizer, 50-60 parts of flame retardant, 1-4 parts of filler, 0.6-1.2 parts of antioxidant, 2.5-3.5 parts of lubricant and 1.5-2.5 parts of cross-linking sensitizer. The high and low temperature resistance of the insulating material can be further improved by optimizing the composition ratio.
[0008] Specifically, the filler is an organic montmorillonite modified by dihydrogenated tallow dimethyl ammonium and siloxane. By modifying the organic montmorillonite with dihydrogenated tallow dimethyl ammonium and siloxane, the double long chain structure can be used to effectively open the layered structure of the montmorillonite, which is beneficial to improving the dispersibility of the organic montmorillonite in the material system.
[0009] Furthermore, the substrate resin is selected from at least one of linear low-density polyethylene and ethylene-vinyl acetate copolymer; the linear low-density polyethylene has a melt index of 0.5-2.5 g / 10 min at 190° C. and a load of 2.16 kg, and a density of 0.9-0.95 g / cm 3 The melt index of the ethylene-vinyl acetate copolymer is 5-6 g / 10 min at 190 ° C and a load of 2.16 kg, and the density is 0.9-1 g / cm 3 , the content of vinyl acetate is 25~28wt%.
[0010] Furthermore, the melt index of the linear low-density polyethylene is 0.5-2 g / 10 min at 190° C. and under a load of 2.16 kg, and the density is 0.91-0.93 g / cm 3 The melt index of the ethylene-vinyl acetate copolymer is 5.5 g / 10 min at 190 ° C and a load of 2.16 kg, and the density is 0.951 g / cm 3 , the content of vinyl acetate is 28wt%.
[0011] Furthermore, the base resin is a mixture of linear low-density polyethylene and ethylene-vinyl acetate copolymer, and the weight proportion of the linear low-density polyethylene is 40-50%, and the weight proportion of the ethylene-vinyl acetate copolymer is 50-60%.
[0012] Furthermore, the compatibilizer is selected from at least one of ethylene-octene copolymer grafted maleic anhydride copolymer and polyethylene grafted maleic anhydride copolymer; the melt index of the polyethylene grafted maleic anhydride copolymer is 0.5-5g / 10min at 190°C and load 5kg, and the grafting rate is between 0.5-1%.
[0013] Furthermore, the melt index of the polyethylene grafted maleic anhydride copolymer is 1-3 g / 10 min at 190°C and a load of 5 kg, and the grafting rate is between 0.9%. The polyethylene grafted maleic anhydride copolymer is used in insulating materials with aluminum hydroxide and magnesium hydroxide as halogen-free flame retardants, which can improve the compatibility and adhesion between the base resin and the inorganic flame retardant interface, thereby maximally improving the flame retardancy of the cable material, reducing the smoke index, smoke volume, calorific value and carbon monoxide generation, increasing the oxygen index, and significantly improving the mechanical properties and thermal properties of the material.
[0014] Furthermore, the flame retardant is selected from at least one of aluminum hydroxide and magnesium hydroxide, wherein the aluminum hydroxide is a micron-sized aluminum hydroxide modified by aminosilane, and the magnesium hydroxide is a micron-sized magnesium hydroxide modified by aminosilane. Using aluminum hydroxide and magnesium hydroxide as flame retardants can greatly improve the dispersion uniformity and enhance the flame retardancy of the insulating material.
[0015] Furthermore, the flame retardant is a mixture of aluminum hydroxide and magnesium hydroxide, and the mass ratio of the aluminum hydroxide to the magnesium hydroxide is 1:1.
[0016] Furthermore, the antioxidant is selected from at least one of the antioxidant 1010 and the antioxidant 168. Furthermore, the antioxidant is a mixture of the antioxidant 1010 and the antioxidant 168, and the mass ratio of the antioxidant 1010 to the antioxidant 168 is 1:1.
[0017] Furthermore, the antioxidant 1010 is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and the antioxidant 168 is tris(2,4-di-tert-butylphenyl)phosphite.
[0018] Furthermore, the lubricant is selected from at least one of calcium stearate and polyethylene wax. Furthermore, the lubricant is polyethylene wax with a molecular weight of 1500 to 5000.
[0019] Furthermore, the cross-linking sensitizer is triallyl isocyanurate.
[0020] The second technical solution adopted by the present invention is: a method for preparing a radiation cross-linked low-smoke halogen-free insulating material, comprising the following steps: (1) Weigh the base resin, compatibilizer, flame retardant, filler, antioxidant, lubricant and cross-linking sensitizer according to certain weight proportions; (2) The raw materials weighed in step (1) are sequentially put into an internal mixer for mixing to obtain a lump-shaped plastic semi-finished product; (3) The conical double forced feeder is used to feed the lumpy plastic semi-finished product into a single screw extruder unit for extrusion granulation, and the natural cooling die surface pelletizing process is used for extrusion granulation to produce radiation cross-linked low-smoke halogen-free insulation material.
[0021] In the preparation method of the present invention, a filler is added in step (1), and the filler is mixed in the lump-shaped plastic semi-finished product through step (2), so as to facilitate the carbonization of the filler and improve the flame retardant and high temperature resistance of the insulating material. The preparation method of the present invention is simple and easy to obtain, and is suitable for industrial mass production.
[0022] Specifically, in step (2), the mixing temperature is 125-145°C, and the mixing time is 10-15 min. In step (3), the temperature of the feeding section of the single-screw extruder is 110-125°C, the temperature of the compression section is 130-145°C, and the temperature of the homogenization section is 135-150°C. DETAILED DESCRIPTION
[0023] The preferred embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more explicit definition of the protection scope of the present invention. It should be noted that the following embodiments are for a better understanding of the present invention, are not limited to the best embodiments, and do not limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0024] It should be noted that, in the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0025] In addition, if the specific experimental steps or conditions are not specified in the examples, the operations or conditions of the conventional experimental steps described in the literature in the art can be carried out. The numerical ranges shown by "~" in the examples indicate the ranges containing the values recorded before and after "~" as the minimum and maximum values, respectively. If the manufacturers of the reagents or instruments are not specified, they are all conventional reagent products that can be obtained commercially.
[0026] The linear low-density polyethylene used in the following examples has a melt index of 0.5-2 g / 10 min at 190°C and a density of 0.91-0.92 g / cm 3The melt index of ethylene-vinyl acetate copolymer at 190°C and load 2.16 kg is 5.5 g / 10 min, and the density is 0.951 g / cm 3 , the vinyl acetate content is 28wt%. The melt index of polyethylene grafted maleic anhydride copolymer at 190℃ with a load of 5kg is 1~3g / 10min, and the grafting rate is 0.9%.
[0027] Example 1 Prepare radiation cross-linked low-smoke halogen-free insulation material as follows: (1) Weigh 34 g of base resin, 4 g of compatibilizer, 52 g of flame retardant, 2 g of filler, 0.8 g of antioxidant, 3.2 g of lubricant and 1.8 g of crosslinking sensitizer respectively; wherein the base resin comprises 44% by weight of linear low-density polyethylene and 56% by weight of ethylene-vinyl acetate copolymer. The compatibilizer is polyethylene grafted maleic anhydride copolymer. The flame retardant comprises micron-sized aminosilane-modified aluminum hydroxide and micron-sized aminosilane-modified magnesium hydroxide in a mass ratio of 1:1. The filler is an organic montmorillonite modified with dihydrogenated tallow dimethyl ammonium and siloxane. The antioxidant comprises pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:1. The lubricant is polyethylene wax with a molecular weight of 1500. The crosslinking sensitizer is triallyl isocyanurate.
[0028] (2) The raw materials weighed in step (1) are sequentially put into an internal mixer and mixed at 130° C. for 15 min to obtain a lump-shaped plastic semi-finished product.
[0029] (3) Feeding the lumpy plastic semi-finished product of step (2) into a single screw extruder through a conical double forced feeder for extrusion granulation, adopting a natural cooling die face pelletizing process for extrusion granulation, and obtaining a radiation cross-linked low-smoke halogen-free insulation material. The temperature of the feeding section in the single screw extruder is 120°C, the temperature of the compression section is 135°C, and the temperature of the homogenization section is 150°C.
[0030] Example 2 Prepare radiation cross-linked low-smoke halogen-free insulation material as follows: (1) Weigh 34g of base resin, 4g of compatibilizer, 55g of flame retardant, 2g of filler, 0.8g of antioxidant, 3.2g of lubricant and 1.8g of crosslinking sensitizer respectively; wherein the base resin comprises 44% by weight of linear low-density polyethylene and 56% by weight of ethylene-vinyl acetate copolymer. The compatibilizer is polyethylene grafted maleic anhydride copolymer. The flame retardant comprises micron-sized aminosilane-modified aluminum hydroxide and micron-sized aminosilane-modified magnesium hydroxide in a mass ratio of 1:1. The filler is organic montmorillonite modified with dihydrogenated tallow dimethyl ammonium and siloxane. The antioxidant comprises pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:1. The lubricant is polyethylene wax with a molecular weight of 1500. The crosslinking sensitizer is triallyl isocyanurate.
[0031] (2) The raw materials weighed in step (1) are sequentially put into an internal mixer and mixed at 130° C. for 15 min to obtain a lump-shaped plastic semi-finished product.
[0032] (3) Feeding the lumpy plastic semi-finished product of step (2) into a single screw extruder through a conical double forced feeder for extrusion granulation, adopting a natural cooling die face pelletizing process for extrusion granulation, and obtaining a radiation cross-linked low-smoke halogen-free insulation material. The temperature of the feeding section in the single screw extruder is 120°C, the temperature of the compression section is 135°C, and the temperature of the homogenization section is 150°C.
[0033] Example 3 Prepare radiation cross-linked low-smoke halogen-free insulation material as follows: (1) Weigh 34g of base resin, 4g of compatibilizer, 58g of flame retardant, 1g of filler, 0.8g of antioxidant, 3.2g of lubricant and 1.8g of crosslinking sensitizer respectively; wherein the base resin comprises linear low-density polyethylene with a weight ratio of 44% and ethylene-vinyl acetate copolymer with a weight ratio of 56%. The compatibilizer is polyethylene grafted maleic anhydride copolymer. The flame retardant comprises micron-sized aminosilane-modified aluminum hydroxide and micron-sized aminosilane-modified magnesium hydroxide in a mass ratio of 1:1. The filler is organic montmorillonite modified with dihydrogenated tallow dimethyl ammonium and siloxane. The antioxidant comprises pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 1:1. The lubricant is polyethylene wax with a molecular weight of 1500. The crosslinking sensitizer is triallyl isocyanurate.
[0034] (2) The raw materials weighed in step (1) are sequentially put into an internal mixer and mixed at 130° C. for 15 min to obtain a lump-shaped plastic semi-finished product.
[0035] (3) Feeding the lumpy plastic semi-finished product of step (2) into a single screw extruder through a conical double forced feeder for extrusion granulation, adopting a natural cooling die face pelletizing process for extrusion granulation, and obtaining a radiation cross-linked low-smoke halogen-free insulation material. The temperature of the feeding section in the single screw extruder is 120°C, the temperature of the compression section is 135°C, and the temperature of the homogenization section is 150°C.
[0036] Comparative Example 1 Prepare radiation cross-linked low-smoke halogen-free insulation material as follows: (1) Weigh 34g of base resin, 4g of compatibilizer, 60g of flame retardant, 0.8g of antioxidant, 3.2g of lubricant and 1.8g of crosslinking sensitizer respectively; wherein the base resin comprises 44% by weight of linear low-density polyethylene and 56% by weight of ethylene-vinyl acetate copolymer. The compatibilizer is polyethylene grafted maleic anhydride copolymer. The flame retardant comprises micron-sized aminosilane-modified aluminum hydroxide and micron-sized aminosilane-modified magnesium hydroxide in a mass ratio of 1:1. The antioxidant comprises pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and tris(2,4-di-tert-butylphenyl)phosphite in a mass ratio of 1:1. The lubricant is polyethylene wax with a molecular weight of 1500. The crosslinking sensitizer is triallyl isocyanurate.
[0037] (2) The raw materials weighed in step (1) are sequentially put into an internal mixer and mixed at 130° C. for 15 min to obtain a lump-shaped plastic semi-finished product.
[0038] (3) Feeding the lumpy plastic semi-finished product of step (2) into a single screw extruder through a conical double forced feeder for extrusion granulation, adopting a natural cooling die face pelletizing process for extrusion granulation, and obtaining a radiation cross-linked low-smoke halogen-free insulation material. The temperature of the feeding section in the single screw extruder is 120°C, the temperature of the compression section is 135°C, and the temperature of the homogenization section is 150°C.
[0039] Performance Testing The radiation cross-linked low-smoke halogen-free insulating materials obtained in Examples 1-3 and Comparative Example 1 were respectively pressed into sheets, and the pressing process was as follows: a flat vulcanizing machine was used, the pressing temperature was 180°C, the preheating time was 12 minutes, the holding time was 6 minutes, and molds of different fixed specifications were used for pressing, and tablets of different specifications with thicknesses of 1 mm, 2 mm, and 3 mm, lengths of 24 mm, and widths of 18 mm were obtained.
[0040] The tablets processed by the tabletting process are subjected to irradiation treatment process: the irradiation dose is 12-16 Mrad, the temperature is 200°C and the load is 0.2 MPa, and after 15 minutes, the thermal extension value is controlled in the range of 20~50%.
[0041] The material properties of the irradiation cross-linked low-smoke halogen-free insulating materials of Examples 1-3 and Comparative Example 1 after sheeting and irradiation treatment were tested. The test results are shown in Table 1.
[0042] Table 1 Test results of Examples 1-3 and Comparative Example 1
[0043] It can be seen from Table 1 that compared with Comparative Example 1, the mechanical properties, aging resistance and low-temperature resistance of the radiation cross-linked low-smoke halogen-free insulating materials prepared in Examples 1-3 are improved after the flame retardant and the filler are compounded, and the flame retardant effect is good and can meet the performance requirements of 125°C temperature-resistant automotive internal wires.
[0044] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A radiation cross-linked low-smoke halogen-free insulation material for automotive internal wires, characterized in that: The invention comprises, by weight: 15 to 55 parts of base resin, 1 to 10 parts of compatibilizer, 45 to 65 parts of flame retardant, 1 to 6 parts of filler, 0.5 to 1.35 parts of antioxidant, 2 to 5 parts of lubricant and 1 to 3 parts of cross-linking sensitizer; wherein the filler is selected from at least one of organic montmorillonite and calcium carbonate silica gel masterbatch.
2. The radiation cross-linked low-smoke halogen-free insulating material according to claim 1, characterized in that: The filler is an organic montmorillonite modified by dihydrogenated tallow dimethyl ammonium and siloxane.
3. The radiation cross-linked low-smoke halogen-free insulating material according to claim 1, characterized in that: The substrate resin is selected from at least one of linear low-density polyethylene and ethylene-vinyl acetate copolymer; the linear low-density polyethylene has a melt index of 0.5-2.5 g / 10 min at 190° C. and a load of 2.16 kg, and a density of 0.9-0.95 g / cm 3 The melt index of the ethylene-vinyl acetate copolymer is 5-6 g / 10 min at 190 ° C and a load of 2.16 kg, and the density is 0.9-1 g / cm 3 , the content of vinyl acetate is 25~28wt%.
4. The radiation cross-linked low-smoke halogen-free insulating material according to claim 3, characterized in that: The substrate resin is a mixture of linear low-density polyethylene and ethylene-vinyl acetate copolymer, wherein the weight proportion of the linear low-density polyethylene is 40-50%, and the weight proportion of the ethylene-vinyl acetate copolymer is 50-60%.
5. The radiation cross-linked low-smoke halogen-free insulating material according to claim 1, characterized in that: The compatibilizer is selected from at least one of ethylene-octene copolymer grafted maleic anhydride copolymer and polyethylene grafted maleic anhydride copolymer; the polyethylene grafted maleic anhydride copolymer has a melt index of 0.5-5 g / 10 min at 190° C. and a load of 5 kg, and a grafting rate of 0.5-1%.
6. The radiation cross-linked low-smoke halogen-free insulating material according to claim 1, characterized in that: The flame retardant is selected from at least one of aluminum hydroxide and magnesium hydroxide, wherein the aluminum hydroxide is micron-sized aluminum hydroxide modified by aminosilane, and the magnesium hydroxide is micron-sized magnesium hydroxide modified by aminosilane.
7. The radiation cross-linked low-smoke halogen-free insulating material according to claim 6, characterized in that: The flame retardant is a mixture of aluminum hydroxide and magnesium hydroxide, and the mass ratio of the aluminum hydroxide to the magnesium hydroxide is 1:
1.
8. The radiation cross-linked low-smoke halogen-free insulating material according to claim 1, characterized in that: The antioxidant is selected from at least one of tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester and tris(2,4-di-tert-butylphenyl) phosphite; the lubricant is selected from at least one of calcium stearate and polyethylene wax; and the crosslinking sensitizer is triallyl isocyanurate.
9. A method for preparing the radiation cross-linked low-smoke halogen-free insulating material according to any one of claims 1 to 8, characterized in that: The steps include: (1) Weigh the base resin, compatibilizer, flame retardant, filler, antioxidant, lubricant and cross-linking sensitizer according to certain weight proportions; (2) The raw materials weighed in step (1) are sequentially put into an internal mixer for mixing to obtain a lump-shaped plastic semi-finished product; (3) The conical double forced feeder is used to feed the lumpy plastic semi-finished product into a single screw extruder unit for extrusion granulation, and the natural cooling die surface pelletizing process is used for extrusion granulation to produce radiation cross-linked low-smoke halogen-free insulation material.
10. The radiation cross-linked low-smoke halogen-free insulation material according to claim 9, characterized in that: In step (2), the mixing temperature is 125-145°C and the mixing time is 10-15 min. In step (3), the temperature of the feeding section of the single-screw extruder is 110-125°C, the temperature of the compression section is 130-145°C, and the temperature of the homogenization section is 135-150°C.